Characterization of Thermophilic Novel-Rare Actinobacteria from Hot Springs and Compost as an Unique Secondary Metabolite Producer - Maghfirah, Ruhul; Kemala, Pati; Astryna, Syarifah Yanti (Journal of Carbazon, 2024)
This review aims to explain in more detail about the Actinobacteria and it secondary metabolites. Some species of Actinobacteria can live in extreme environments such as high acid, high base, high salt and even high temperatures. Actinobacteria mainly of the genus Streptomyces sp. has been known to produce bioactive compounds such as antibacterial, antifungal, anticancer, antitumor, anticytotoxic, anti-inflammatory, anti-parasitic, anti-malarial, antiviral and antioxidant. This study reviews various research findings on Actinobacteria species and their ability to thrive in extreme environments. It also reviews the findings of bioactive compounds isolated from Actinobacteria and their potential applications. Some species in the genera Streptomyces, Thermonospora, and Thermoactinomyces have optimal growth temperatures above 55C and are categorized as thermophilic. More than 30,000 bioactive compounds that have been isolated are derived from Actinobacteria and 80% are from the genus Streptomyces sp. Benzastatin C and 3-Chloro-Tetrahidroquinolon are new antivirals isolated from Streptomyces nitrosporeus. Essramycin is a novel antibiotic that shows activity against Gram positive and Gram negative bacteria. Chandrananimycin A isolated from Actinomadura sp. and N-(2-hydroxyphenyl)-2-Phenazinamin (NHP) isolated from Nocardia dassonvillei are novel antibiotics that can be used as antifungals, antialgas, antibacterials and anticancer. The potential of Actinobacteria in producing bioactive compounds can advance the field of science and technology in the future and become an alternative to overcome the problem of resistance to pathogenic microorganisms are increasing.